2012
DOI: 10.5115/acb.2012.45.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglial cells synthesize and secrete AGE-albumin

Abstract: A holy grail of curing neurodegenerative diseases is to identify the main causes and mechanisms underlying neuronal death. Many studies have sought to identify these targets in a wide variety of ways, but a more important task is to identify critical molecular targets and their origins. Potential molecular targets include advanced glycation end products (AGEs) that can promote neuronal cell death, thereby contributing to neurodegenerative disorders such as Alzheimer disease or Parkinson disease. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Finally, it is worth reporting that it has recently been shown that glial cells in the CNS can produce albumin [7,[38][39][40], but how much this contributes to the total CSF albumin concentration is still being debated. QAlb, therefore, still remains the only validated laboratory tool for assessing B-CSF-B permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth reporting that it has recently been shown that glial cells in the CNS can produce albumin [7,[38][39][40], but how much this contributes to the total CSF albumin concentration is still being debated. QAlb, therefore, still remains the only validated laboratory tool for assessing B-CSF-B permeability.…”
Section: Discussionmentioning
confidence: 99%
“…These results are also similar with those for AD and alcoholic brains. [21][22][23] Next, we investigated whether AGE-albumin is key for inducing dopaminergic neuronal death in LUMHES cells. The International Journal of Nanomedicine is an international, peerreviewed journal focusing on the application of nanotechnology in diagnostics, therapeutics, and drug delivery systems throughout the biomedical field.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that only AGE-albumin has microglia-specific expression in pathological conditions such as AD. [20][21][22] To determine the AGE-albumin synthesis and secretion in activated microglial cells, we evaluated whether AGE-albumin synthesis and secretion are elevated by α-synuclein ( Figure 3A). After α-synuclein exposure, human microglial cells showed significant elevation of AGE-albumin.…”
Section: Activated Microglial Cells Synthesize and Secrete Age-albuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of AGE receptors (RAGE) increases ROS formation and leads to activation of NF-κB pathway. This ultimately promotes the expression of a variety of pro-inflammatory mediators [2,122,130,131] thus adjuvanting/strengthening the immune and pro-inflammatory responses. In fact increased accumulation of AGEs in Alzheimer’s patients has proven to cause neuronal death and degeneration, thereby supporting the fact that diabetes increases the risk of AD and any shift in normal glucose metabolism is deleterious for BBB integrity.…”
Section: Oxidative Stress At Bbb In Dmmentioning
confidence: 99%